IMPLEMENTASI PROFIT AND LOSS SHARING PADA AKAD KERJA SAMA DI TAMBAK GARAM MARENGAN DITINJAU DARI KONSEP EKONOMI ISLAM - Maghfiroh, Saodatul (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2022)
Abstract: Marengan Village is one of the villages in Kalianget District, Sumenep Regency. Kaliangetsub-district is the sub-district with the largest contributor to salt production in Sumenep district and one ofthem is in Marengan village where some of the people use a cooperation agreement with the Profit And LossSharing system or profit sharing which in Islamic economics is known as Mudharabah. This study aims toexamine more deeply about the Mudharabah contract in an Islamic economic perspective and to find outhow the implementation of cooperation for salt aquaculture profits with the Mudharabah contract inMarengan village, Kalianget sub-district, Sumenep district. This research uses descriptive qualitativeresearch. Data sources consist of secondary data and primary data. Methods of collecting data wereinterviews, observations and documentation of related sources. The data processing and data analysistechniques used in this study were qualitative techniques. The results of this study indicate that some saltfarmers in Marengan village use the mudharabah cooperation agreement with the paron system with theprovisions of 1/3 for mudharib 2/3 for shohibul mall where all costs come from the owner of the capital.In this collaboration, it only uses a profit-sharing system while the losses are borne by the owners of thecapital, meaning that if there is a loss that is borne by Shohibul Mall, this is very rare in the Marenganarea.Keywords: profit sharing, mudharabah, Marengan village